REFLECTIONS OF DANCE ALONG THE BRAHMAPUTRA celebrating dance in North East India - Buck, Ralph; Snook, Barbara, 1946-; Nath, Debarshi Prasad ([S.l.] : ROUTLEDGE, 2023)
This volume brings a critical lens to dance and culture within North East India. Through case studies, first-hand accounts, and interviews, it explores unique folk dances of Indigenous communities of North East India that reflect diverse journeys, lifestyles, and connections within their ethnic groups, marking almost every ritual and festival. Dance for people of North East India, as elsewhere, is also a way of declaring, establishing, celebrating, and asserting humans' relationship with nature. The book draws attention to the origins and special circumstances of dances from North East India. It discusses a range of important folk-dance forms alongside classical dance forms in North East India, with a focus on Sattriya dance. Thechapters examine how these dance forms play an important role in the region's socio-cultural, economic, and political life, intertwining religion and the arts through music, dance, and drama. Further, they also explore how folk dance cultures in North East India have never been relegated to the background, never considered secondary, aesthetically, or otherwise, but have become expressions of political and cultural identity. An evocative work, this volume will be of interest to students and researchers of pedagogy, choreography, community dance practice, theatre and performance studies, social and cultural studies, aesthetics, interdisciplinary arts, and more. It will be an invaluable resource for artists and practitioners working in dance schools and communities.
Keywords: PERFORMING ARTS / Dance / Folk; Dance -- India, Northeastern